Aggregate Productivity Effects of Road Investment - A Reassessment for Western Europe - Andreas Kopp (European Regional Science Association (ERSA), 2005)
The paper investigates the productivity effects of national road infrastructure investment in Western Europe.The study makes use of newly available OECD/ECMT data showing a secular decline of productivity growth and of transport infrastructure investment. Infrastructure availability is modelled like an unpaid shadow factor allowing for more than constant aggregate returns to scale while firms operate with linear homogenous production functions, with transport as an input. Productivity increases are measured by the Toernquist index The link between road investment and macroeconomic productivity is studied using a new econometric technique to avoid the identification problem that discredited the early literature. The results show that there is no clear over- or underinvestment. The aggregate level of road investment seems to be such that the implied rate of return is close to the opportunity cost of private capital.
Keywords: 330